Aplikasi Metode Quality Function Deployment dalam Mengevaluasi Kualitas Pelayanan Dosen Kepada Mahasiswa - Leli Deswindi; Luis Andersen (Universitas Bunda Mulia, 2017)
World events and technology are so rapid as well as science demands that higher education makes a very important and must be fulfilled by various circles of society, therefore the quality of service and quality of education is an issue which is to be noted for the institution - higher education institutions to produce graduates who can compete and excellent in the world of work. The purpose of this study was to determine the quality of faculty service quality as what is desired by students, and prioritize efforts to improve teacher performance to student services based on Quality Function Deployment method, as for the object of this research is the University of XYZ. In this study researchers used a method Quality Function Deployment, which is where the primary data obtained, among others, interviews, field research and questionnaire data obtained through the questionnaires to the students. This study also used some secondary data, which include literature research, and techniques of documentary studies. In order to evaluate and improve the quality of teaching services provided to students, the researchers first conduct an analysis of what lecturers services desired by students, and the subsequent results of the analysis will be processed by using House of Quality matrix, the matrix which contains about degree of importance to the technical parameters of interaction that must be done to improve the quality of teaching services. From the analysis results of research using Quality Function Deployment method, the obtained factor of development priorities that have been conducted by the University of XYZ to evaluate and improve the quality of teaching services to students at XYZ University in accordance with the current priorities of the service quality factors obtained from this research.Keywords: Service Evaluation, Quality Function Deployment